PREDIKSI FINANCIAL DISTRESS PERUSAHAAN DI INDONESIA MENGGUNAKAN RASIO KEUANGAN DAN ANALISIS DISKRIMINAN - Kusuma, Januaryco; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2021)
This study aims to identify and explain financial ratios that have an influence on the formation of financial distress prediction models in companies in Indonesia. Knowing and explaining the process of forming models using financial ratios and processing them with discriminant analysis methods.The population in this study are all sectors of companies listed on the Indonesia Stock Exchange as a public company and have the data used, namely the financial ratios and financial condition of the company. There are 58 samples divided into 2 categories, namely companies experiencing financial distress and companies that do not. Data analysis used descriptive statistical analysis, classical assumption test, and discriminant analysis.The results of the research model have a sufficient level of accuracy and financial ratios have an influence on model formation.